2017
DOI: 10.2500/ar.2017.8.0202
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topical Beclomethasone on Inflammatory Markers in Adults with Eosinophilic Esophagitis: A Pilot Study

Abstract: Background:Topical corticosteroids have proven efficacy in the treatment of eosinophilic esophagitis (EoE) and are considered the cornerstone of therapy.Objective:To evaluate the effect of topical beclomethasone dipropionate (BDP) therapy on clinical outcomes, esophageal eosinophilia, and other markers of inflammation in patients with EoE.Methods:Nine subjects with a biopsy-proven diagnosis of EoE were enrolled. In a cross-over design, the subjects were randomly assigned to a sequence of BDP and placebo. Treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…RCTs were excluded if they did not have an explicit glucocorticosteroid vs placebo comparison, 27,[49][50][51] and if they did not include budesonide or fluticasone in the treatment group. 52 Six meta-analyses were reviewed and excluded because they did not include the most recent RCTs published in the field, or included studies in addition to a placebo/glucocorticosteroid comparison. After discussion among the expert panel, the following decisions were made regarding how to pool the data: a single pooled estimate is presented despite differences in type of glucocorticosteroid, delivery mechanism, dosages, patient population (adult/pediatric), and manner of outcome reporting (peak vs mean counts).…”
Section: Discussionmentioning
confidence: 99%
“…RCTs were excluded if they did not have an explicit glucocorticosteroid vs placebo comparison, 27,[49][50][51] and if they did not include budesonide or fluticasone in the treatment group. 52 Six meta-analyses were reviewed and excluded because they did not include the most recent RCTs published in the field, or included studies in addition to a placebo/glucocorticosteroid comparison. After discussion among the expert panel, the following decisions were made regarding how to pool the data: a single pooled estimate is presented despite differences in type of glucocorticosteroid, delivery mechanism, dosages, patient population (adult/pediatric), and manner of outcome reporting (peak vs mean counts).…”
Section: Discussionmentioning
confidence: 99%
“…Other topical corticosteroids, such as beclomethasone or momethasone, have been studied only in small, mostly uncontrolled, trials. 2325…”
Section: Evolution and Current Role Of Topical Corticosteroids In Eoementioning
confidence: 99%
“…In contrast, only 13 reported RCTs (59.1%) and four (40%) registered trials defined a priori endoscopic endpoints. Exploratory outcomes were evaluated in 68.2% of reported RCTs (15/22) and included (1) serum or tissue biomarkers (including MIB-1/Ki-67, 19 interleukin [IL] 5, 22,25 IL13, 25,27,35 eotaxin, 22,30 tryptase for mast cells, 19,21,23,25,27,29 tumor necrosis factor, 21,22 tenascin C, 21,27 cytokeratin, 21,23 terminal deoxynucleotidyl transferase-mediated deoxyuridine triphosphate nickend labeling positive inflammatory and epithelial cells, 21,23 transforming growth factor beta (TGFb), [20][21][22][23]25,27 CD3/8, 19,[21][22][23] eosinophil cationic protein, [21][22][23] eosinophil derived neurotoxin, 22,24 eosinophil peroxidase, 27 serum immunoglobulins, 29 and thymic stromal lymphopoietin 35 ); (2) esophageal thickness 23 (as measured on endoscopic ultrasound); (3) genetic factors associated with EoE (including single nucleotide polymorphisms of TGF-b 20 and measures of the EoE transcriptome 28,30…”
Section: Outcome Reportingmentioning
confidence: 99%
“…Fourteen studies reported change in absolute eosinophil counts before and after therapy or by percentage changes from baseline in eosinophil density. 23,24,[26][27][28][29][30]32,33,35,[37][38][39][40] One study used the EoE Histology Scoring System (EoE-HSS) to evaluate both severity and extent of 8 features (eosinophil density, basal zone hyperplasia, eosinophil abscesses, eosinophil surface layering, dilated intercellular spaces, surface epithelial alteration, dyskeratotic epithelial cells, and lamina propria fibrosis). 38 Four studies specified that histologic outcomes required changes at multiple esophageal levels (eg, proximal and distal esophagus).…”
Section: Histology Outcome Definitionsmentioning
confidence: 99%